A influência da proporção de material fresado na mistura asfáltica - Aliano, Ângela Beck (My University, 2025)
The use of recycled asphalt pavements has gained prominence as a sustainable, economical, and certified solution for modern road engineering practices.This study aimed to evaluate the behavior of asphalt mixtures with the addition of different proportions of Reclaimed Asphalt Pavement (RAP). RAP, a residue from pavement milling, is an efficient alternative in terms of economics and the use of new materials, but research indicates that its excessive dosage can lead to loss of flexibility and increased susceptibility to fatigue cracking. The overall objective was to evaluate the performance of the mixture by analyzing its mechanical properties. The methodology included the complete characterization of the milled material (granulometry and binder content) and the production of asphalt mixtures with proportions of 0% (reference), 10%, and 20% replacement of virgin aggregates with RAP. These mixtures were subjected to laboratory tests of stability, creep, and Diametral Compression Tensile Strength (DCTS). The study showed that the addition of RAP significantly modifies the behavior of asphalt mixtures. Stability, creep, and tensile strength analyses indicated that 10% RAP tends to reduce mechanical performance, as this amount is insufficient to improve the stiffness and cohesion of the mixture. On the other hand, 20% RAP increased stability and tensile strength, reflecting greater stiffness due to the aged binder present in the milled material. Despite this, the increased stiffness may reduce deformability and affect pavement durability. Thus, it is concluded that higher RAP contents can improve some properties, but require adjustments to the virgin binder content and possibly the use of a rejuvenating agent to maintain a balance between strength, flexibility, and long-term performance. [resumo fornecido pelo autor]
A utilização de pavimentos asfálticos reciclados tem ganhado destaque por representar uma solução sustentável, econômica e alinhada às práticas modernas de engenharia rodoviária. O presente trabalho buscou avaliar o comportamento da mistura asfáltica com a adição de diferentes proporções de Pavimento Asfáltico Recuperado (RAP). O RAP, um resíduo da fresagem de pavimentos, é uma alternativa eficiente em termos econômicos e de uso de novos materiais, mas pesquisas indicam que sua dosagem excessiva pode levar à perda de flexibilidade e ao aumento da suscetibilidade à formação de trincas por fadiga. O objetivo geral foi avaliar o desempenho da mistura, analisando suas propriedades mecânicas. A metodologia incluiu a caracterização completa do material fresado (granulometria e teor de ligante) e a produção de misturas asfálticas com proporções de 0% (referência), 10% e 20% de substituição de agregados virgens por RAP. Essas misturas foram submetidas a ensaios laboratoriais de estabilidade, fluência e Resistência à Tração por Compressão Diametral (RTCD). O estudo mostrou que a adição de RAP modifica de forma significativa o comportamento das misturas asfálticas. As análises de estabilidade, fluência e resistência à tração indicaram que 10% de RAP tende a reduzir o desempenho mecânico, já que essa quantidade não é suficiente para melhorar a rigidez e a coesão da mistura. Por outro lado, 20% de RAP aumentou a estabilidade e a resistência à tração, refletindo maior rigidez devido ao ligante envelhecido presente no material fresado. Apesar disso, o aumento da rigidez pode reduzir a deformabilidade e afetar a durabilidade do pavimento. Assim, conclui se que teores mais elevados de RAP podem melhorar algumas propriedades, mas exigem ajustes no teor de ligante virgem e, possivelmente, o uso de rejuvenescente para manter o equilíbrio entre resistência, flexibilidade e desempenho em longo prazo. [resumo fornecido pelo autor]
Keywords: Pavimentos; Engenharia civil